Balancing Resource Exploitation and Conservation: Indigenous Practices in Bintuni Bay, West Papua - Saefullah, Rifki; Sandi S, Renda; Azkiyah , Hilda (Communication in Research and Publications (CRP), 2024)
West Papua is recognized as one of the regions with the highest biodiversity globally. Alongside this natural richness, the indigenous communities in areas such as Bintuni Bay have developed traditional ecological knowledge that has allowed them to manage the environment sustainably. These practices are passed down through generations and are reinforced by customary laws, taboos, and cultural rituals that remain relevant in modern times. However, increasing pressures from modernization, land clearance for plantations, mining, and infrastructure projects are posing significant threats to these traditional practices and ecological sustainability. This study explores the role of indigenous knowledge in environmental management, examining the balance between resource exploitation and conservation, disaster mitigation strategies, and the protection of cultural heritage.